Theory of Complexity: discursive functioning in academic productions on Environmental Education in school contexts - Araujo, Adelmo Fernandes de; Morais, Wanderson Rodrigues [UNESP]; Silva, Orlane Fernandes (Federal Univ Rio Grande, Inst Education, 2022)
The aim of this work is to analyze the discursive functioning in statements that are supported by Edgar Morin's contributions to the understanding of studies on Environmental Education (EE) that were carried out in the school environment. The research corpus consisted of clippings from theses and dissertations on EE gathered by the EArte Project. In order toanalyze such materialities, we relied on the french materialist Discourse Analysis by Michel Pecheux and collaborators. As result, we identified that the mechanisms used by the authors range from pre-constructed effects, as well as transverse-discourses, in which the authors mobilized a wide range of themes from the theory of complexity, proving to be a reference that dialogues with EE; as well as lack of referential stability of some expressions.
Keywords: Environmental Education; Edgar Morin; Discourse Analysis